Mineral elements in milk and dairy products - Šimun Zamberlin; Neven Antunac; Jasmina Havranek; Dubravka Samaržija (Mljekarstvo)
Mineral elements occur in milk and dairy products as inorganic ions and salts, as well as part of organic molecules, such as proteins, fats, carbohydrates and nucleic acids. The chemical form of mineral elements is important because it determines their absorption in the intestine and their biological utilization. The mineral composition of milk is not constant because it depends on lactation phase, nutritional status of the animal, and environmental and genetic factors. The objective of this research is to point out the research results of chemical form, content and nutritional importance of individual mineral elements that are present in various milks and dairy products.